2021
DOI: 10.1007/s00170-021-07211-2
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of machining feedrate and cycle times considering interpolator dynamics

Abstract: This paper presents an accurate machining feedrate prediction technique by modelling the trajectory generation behaviour of modern CNC machine tools. Typically, CAM systems simulate machines’ motion based on the commanded feedrate and the path geometry. Such approach does not consider the feed planning and interpolation strategy of the machine’s numerical control (NC) system. In this study, trajectory generation behaviour of the NC system is modelled and accurate cycle time prediction for complex machining too… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For instance, the surface quality of parts can be estimated in parallel to the process within a GPU-enabled (graphical processing unit) material removal simulation with a subsequent virtual measurement, which significantly reduces the latency between machining and the detection of defective parts [166,167]. A sufficiently accurate virtual representation of the machining process [26,[168][169][170][171]] also enables cause-and-effect analysis and, therefore, robust process design and control [172][173][174][175][176] as well as the exploitation of potential process productivity [177]. Further cases of production processes with knowledge-based approaches include welding [178,179], injection molding [180,181], linear winding [182], tape laying [183], metal forming [184], laser polishing [185], automated fiber placement [186], sheet molding compound [187], fused filament fabrication [188], and metal additive manufacturing (AM) [189][190][191][192][193].…”
Section: General Developmentsmentioning
confidence: 99%
“…For instance, the surface quality of parts can be estimated in parallel to the process within a GPU-enabled (graphical processing unit) material removal simulation with a subsequent virtual measurement, which significantly reduces the latency between machining and the detection of defective parts [166,167]. A sufficiently accurate virtual representation of the machining process [26,[168][169][170][171]] also enables cause-and-effect analysis and, therefore, robust process design and control [172][173][174][175][176] as well as the exploitation of potential process productivity [177]. Further cases of production processes with knowledge-based approaches include welding [178,179], injection molding [180,181], linear winding [182], tape laying [183], metal forming [184], laser polishing [185], automated fiber placement [186], sheet molding compound [187], fused filament fabrication [188], and metal additive manufacturing (AM) [189][190][191][192][193].…”
Section: General Developmentsmentioning
confidence: 99%
“…As an alternative measuring technique for tool geometry accuracy monitoring, it was proposed to use a trigger touch probe integrated into the NC control system [17] or laser measuring tools or interferometers to control angular errors, horizontal and vertical straightness errors, parallelism errors [18], and squareness errors [19]. Another way to affect and improve machining accuracy is to predict feed rate and cycle times considering interpolator dynamics using a finite impulse response-based low pass filter, which estimated more than 90% more accurate cycle times than CAM-based prediction [20]. Holub et al found that the roundness of the machined surface when milling on a CNC machine can be improved by 40% using volumetric compensation accompanied by a LaserTRACER self-tracking interferometer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore to model the non-stop interpolation behavior of modern NC systems significant research has been conducted in non-stop interpolation and geometric blending methods. The research spans from circular arcs, cubic [12] and quintic splines [13] through to modern Finite Impulse Response based filtering methods [14] [15].…”
Section: Introductionmentioning
confidence: 99%